Metal-phenolic networks spontaneously reinforced carrageenan-based packaging films with antibacterial and antioxidant properties - Shi, Shuo; Lan, Xi; Ding, Xiyan; Han, Ximei; Sun, Jing; Wang, Jianlong; Duan, Jinyou (International journal of biological macromolecules, 2024)
The burdens of microbial food safety and environmental contamination make it necessary to search sustainable, safe, antibacterial and antioxidant active food packaging materials. This contribution proposed the use of copper-ferulic acid networks (CuFA NWs) as antibacterial substances. By immobilizing CuFA NWs into carrageenan matrix, a CuFA network-reinforced carrageenan-based packaging film (Carr/CuFA) was obtained via spontaneously hydrogen bond and electrostatic interaction indicated by ATR-IR and XPS. Interestingly, the addition of CuFA NWs increased the mechanical strength, surface hydrophobicity, and water vapor barrier properties of the carrageenan-based film, and imparted the film with UV-shielding capacity. Importantly, the Carr/CuFAx film exhibited effective antioxidant activity, and antibacterial performance against four foodborne bacteria. As a result, after confirming the safety of Carr/CuFA3 films by releasing, hemolysis and cell viability experiments, the Carr/CuFA3 film exhibited great potential in the safety control and preservation of fresh fruit by using blueberry and cherry as model fruit. In summary, this work provides a feasible candidate for the preservation and contamination control of fresh fruit. [Display omitted]